DIELECTRIC STUDIES ON TSP: NANO3 BIOPOLYMER-BASED POLYMER ELECTROLYTES - M. Gnana Kiran; Sharmila. D; Rao M. C.; Naveen Kumar. V; Krishna Jyothi. N (Proceedings on Engineering Sciences)
The solution cast method made free-standing tamarind seed polysaccharide (TSP): Sodium Nitrate (NaNO3) based solid polymer electrolyte films with various weight percentages. The conductance and dielectric properties of the polymer films were evaluated using AC impedance spectroscopy. This polymer electrolyte's conductance varied with temperature. By raising the temperature for different concentrations, the conductivity was increased. The maximum conductivity was obtained for 70:30 films at 373 K. According to dielectric studies, dielectric constants and dielectric loss were higher at low frequencies and lower at higher frequencies. At 303 K, the dielectric constant (ε1) was 899.1, and the dielectric loss (ε11) was 1393.8 for 70:30 (TSP: NaNO3) composition. The minimal tangent loss was 1.54x10-4 for 30% film.